Dialects of Faith: Pluralism and Poetic Translation in F. Max Müller's Sacred Books of the East - Brorby, Joshua (Religion & literature, 2024)
Philologist and religious comparativist F. Max Müller's Sacred Books of the East (1879-1910), a fifty-volume collection of translations into English from the texts of seven "Eastern" religions, exemplifies the shifting nature of pluralism in the Victorian period. Considering Müller's introduction to the SBE alongside his well-known lectures on religion and language, this article shows that for Müller the poetic capacity to translate non-Christian scriptures was linked to his own belief in the logos theory, Protestant supersessionism, and the partial inspiration of sacred texts across traditions. Under a united scientific vision of religious and linguistic evolution, he posited a view of religious commensurability in which faiths are "dialects" of a shared yearning for the divine. But the SBE also shows how a scientific conception of religion depended on a poetic praxis of translation by which translators might claim authority as both favored mediators of texts from Sanskrit, Chinese, Pāli, and other languages, and inheritors of a Romantic literary tradition. In expanding the categories of inspiration and scripture at issue in the 1860s, the SBE reminds us that nineteenth-century attempts at constructing a global history of religions - and far-reaching global systems in general - at once instantiated and abraded the codifying logic of imperialism. With the SBE, Müller asserted a poetics of religion across traditions and eras that reflected his deeply held universalist beliefs yet remained mired in the hopefulness typical of his Victorian milieu.